The role of extracorporeal membrane oxygenation in patients after irreversible cardiac arrest as potential organ donors - Kłosiewicz, Tomasz; Puślecki, Mateusz; Zieliński, Marcin; Mandecki, Michał; Ligowski, Marcin; Stefaniak, Sebastian; Dąbrowski, Marek; Karczewski, Marek; Gąsiorowski, Łukasz; Sip, Maciej; Dąbrowska, Agata; Telec, Wojciech; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
The number of people waiting for a kidney or liver transplant is growing systematically. Due to the latest advances in transplantation, persons after irreversible cardiac arrest and confirmation of death have become potential organ donors. It is estimated that they may increase the number of donations by more than 40%. However, without good organization and communication between pre-hospital care providers, emergency departments, intensive care units and transplantation units, it is almost impossible to save the organs of potential donors in good condition. Various systems, including extracorporeal membrane oxygenation (ECMO), supporting perfusion of organs for transplantation play a key role. In 2016 the “ECMO for Greater Poland” program was established. Although its main goal is to improve the survival rate of patients suffering from life-threatening cardiopulmonary conditions, one of its branches aims to increase the donation rate in patients with irreversible cardiac arrest. In this review, the role of ECMO in the latter group as the potential organ donors is presented.